Qualidade de dados e Linked Data: aprimoramento de dados abertos governamentais - Machado, Emanuelle (2025)
The growing demand for transparency and accessibility in the availability of educational data has driven the search for strategies to improve its publication quality. In this context, this study focuses on the UTFPR open data repository, analyzing related works and examining the available information to identify its limitations and propose improvements. In particular, it highlights how data interoperability can benefit from the use of the semantic web and ontologies. The analysis revealed challenges such as the lack of standardized metadata, the use of restrictive formats, outdated data, and difficulties in integrating with other systems, compromising data reuse and accessibility. By suggesting directions for improvement, this study aims to contribute to a more efficient management of educational data and foster research that expands the positive impact of people’s interaction with such information, promoting benefits for society and the dissemination of knowledge.